ASPEK-ASPEK PENCIPTAAN TARI DALAM PENDIDIKAN - Treny Hera (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The essence of dance education speaks of human beings as creators, actors and art users about how to plant, build, and develop the knowledge gained through art education in particular. The art of dance is created and created on the basis of desire and desire to work born from the idea of human creativity that is educated. Indeed the work of dance is a manifestation of the results of human ideas through the motion is arranged through the process of exploration, experience of art, education, until the excavation of meaning and purpose. Through the creation of art activities in education to be a container to express the idea of creativity of educators and learners. The activities of dance performed by humans in arranging dance, creating dance to dance in a performance context. Based on that, it is necessary to analyze the aspect of dance creation in education.  Keywords— Aspects of Dance Creation, Education. Abstrak— Hakikat pendidikan seni tari berbicara mengenai manusia sebagai pencipta, pelaku dan pemakai seni mengenai bagaimana cara menanam, membangun, dan mengembangkan ilmu pengetahuan yang diperoleh melalui pendidikan seni khususnya. Seni tari tercipta dan diciptakan atas dasar keinginan dan hasrat berkarya yang lahir dari ide kreatifitas manusia yang berpendidikan. Sejatinya karya tari merupakan wujud nyata hasil gagasan manusia melalui gerak yang ditata melalui proses eksplorasi, pengalama berkesenian, pendidikan, hingga penggalian makna dan tujuannya. Melalui aktivitas penciptaan seni di dalam pendidikan menjadi wadah mengekspresikan ide kreatifitas pendidik dan peserta didik. Aktivitas seni tari dilakukan manusia dalam hal menata tari, mencipta tari hingga menari dalam suatu konteks pertunjukan. Berdasarkan itulah perlu dilakukan analisis terhadap aspek penciptaan tari di dalam pendidikan. Kata Kunci— Aspek Penciptaan Tari, Pendidikan.